Radiographic study of ossification of the pterygospinous and pterygoalar ligaments by the Hirtz axial technique. - Rosa, Rafaela R (2010)
The correct radiographic identification of ossification of the pterygospinous and pterygoalar ligaments plays an important role in surgical procedures for the treatment of trigeminal neuralgia. Most of these procedures are performed through the foramen ovale, a site where these ligaments can be found to be partially or completely ossified. We studied the radiographic features of these ossified ligaments and their location in relation to the foramen ovale by the Hirtz axial technique. For this purpose, 93 dry skulls from the Discipline of Anatomy, São José dos Campos Dental School, UNESP, which presented partial or complete ossification of these ligaments, were radiographed. The pterygospinous ligament was detected on 27.97% of radiographs and was partially ossified in 19.36% of cases and completely ossified in 8.61%. The pterygoalar ligament was present in 62.35% of radiographs, being partially ossified in 49.44% and completely ossified in 12.91%. The pterygospinous ligaments was found to be partially and completely ossified on the same radiograph in 3.23% of cases, whereas the pterygoalar ligament appeared partially and completely ossified on the same radiograph in 6.45%. Furthermore, the pterygospinous ligament was thinner than the pterygoalar ligament and located more medially in relation to the foramen ovale. The pterygoalar ligament formed a large bone bar lateral to the foramen ovale, often obliterating the lumen of the latter. The Hirtz axial technique is an excellent tool for the observation of complete or partial ossification of the pterygospinous and pterygoalar ligaments in surgical procedures for the treatment of trigeminal neuralgia performed through the foramen ovale.